Can CO2 Emission Reduction and Economic Growth Be Compatible? Evidence From China - Zhang, Zhuang; Chen, You-Hua; Wang, Chien-Ming (Frontiers in Energy Research, 2021)
Clean energy is widely concerned for its low carbon emission and renewability. Using provincial panel data in China from 2000 to 2017, this work investigated the aggregate effects of clean electricity. The results showed that: (1) When the ratio of clean electricity in total electricity increases by 1%, GDP per capita will increase by 0.16% and CO2 emissions will decrease by 0.848%. In other words, clean electricity can achieve the goal of low-carbon economic development and self-supply. Self-supply of clean energy, rather than trade and efficiency, is the main reason for its boosting economic growth. (2) Clean electricity increases the regional economic gap in China. The effects of pollution inhibition and economic promotion of clean electricity in developed areas are significantly greater than those in less developed areas. Thus, clean energy policy in China should not only make benefical to the economic development, but also avoid the excessive economic gap between regions. Policy makers should not only vigorously promote the clean power revolution, but also pay attention to the inclination of energy policy to the central and western regions.